REGRESSION AND PRINCIPAL COMPONENT ANALYSIS TO STUDY STABILITY AND ADAPTABILITY IN SOYBEAN - PELÚZIO, Joênes Mucci; FIDELIS, Rodrigo Ribeiro; GIONGO, Pedro Rogério; SILVA, Joseanny Cardoso da; CAPPELLARI, Daniel CAPPELLARI; BARROS, Hélio Bandeira (Scientia Agraria, 2008)
This work aimed to evaluate the performance, adaptability and stability of soybean genotypes in five environments at the state of Tocantins, Brazil. The trials were carried out in the 2004/05 and 2005/06 growing season at the counties of Alvorada and Gurupi-TO. The experimental design was a randomized complete block with three replicates. To evaluate stability and adaptability of the genotypes, the EBERHART and RUSSELL (1966) and centroid methods were used. The average grain yield varied from 2112 kg ha-1 (Gurupi III) to 3112 kg ha-1 (Alvorada I), with an general average of 2678 kg ha-1. According to the EBERHART and RUSSELL(1966), and centroid methodologies, the cultivar M-SOY 8925 was recommended to the wide range of environmental conditions of the state of Tocantins. Based on the centroid method, the cultivar P98N82 showed the best performance to grown in specific conditions of favorable environments.